Body image of healthy adolescent women and its association with physical activity: a systematic review - Rica, Roberta Luksevicius; Bocalini, Danilo Sales; Jesus Miranda, Maria Luiza de; Valenti, Vitor Engracia [UNESP]; Gama, Eliane Florencio (Abrasco, 2018)
The aim of this study was to evaluate the related scientific production on body image in healthy female adolescents and its association with physical activity. A systematic review of national and international journals was conducted using the major electronic databases. The following inclusion criteria selection were used: sample of female adolescents, with different results; papers in English, Spanish and Portuguese; papers published from 2005 to 2015. Eighteen studies were included and carefully analyzed. The most published paper concentrations were found in Europe (61.2 %). Several studies (95%) used questionnaires as a research instrument to assess physical activity and 55% studies used scales to analyze the body image. No increase was found in the production of literature involving body image study and physical active behavior in healthy female adolescents. In conclusion, the main findings of this review relate to the lack of parameters for the measurement of physical activity and body image analysis. Thus, although it is a current thematic area in the literature, it is possible to consider that the diversity of methodological design between studies makes it difficult to compare the data, making it imperative to standardize instruments and definitions.
Keywords: Physical activity; Body image; Adolescents